Trends in the Transitory Variance of Earnings: Evidence from Sweden 1960-1990 and a Comparison with the United States - Magnus Gustavsson (Uppsala University, Department of Economics, 2004)
I decompose the cross-sectional variance of male annual earnings in Sweden between 1960 and 1990 into permanent and transitory components. The transitory variance increased until the early 1970s, declined during the remainder of the decade and then rose again during the second half of the 1980s. The permanent variance declined over the whole sample period but its decrease was much more rapid up until the early 1980s than afterwards. Comparing the results for the transitory variance with evidence from the U.S. reveals sharp differences. Most notably, the transitory variance of U.S. earnings rose sharply from the mid 1970s to the mid 1980s. An important explanation for these dissimilarities appears to be labor market institutions. In particular, it is likely that centralized solidarity bargaining in Sweden imposed constraints on earnings instability during the 1970s and early 1980s.
Keywords: C33; D31; J39; 330; Earnings dynamics; Earnings inequality; Panel data; Lohn; Schweden; Maßzahl